AI-INTEGRATED STEM-PBL TRAINING: PENGUATAN TPACK GURU SMP DI KABUPATEN MAJALENGKA - Ella Fitriani; Fera Kurniadewi; Hanhan Dianhar; Ariyatun; Alifah Deslia; Patrisia Maghfira (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2025)
Perkembangan kecerdasan buatan (Artificial Intelligence/AI) membuka peluang besar bagi inovasi pembelajaran STEM (Science, Technology, Engineering, and Mathematics) berbasis Problem-Based Learning (PBL). Secara umum, guru masih menghadapi tantangan dalam mengintegrasikan teknologi ini ke dalam praktik pembelajaran, khususnya bagi mereka yang bertugas di wilayah yang relatif jauh dari perkotaan meskipun fasilitas pendidikan sudah tersedia. Keterbatasan pemahaman dan keterampilan dalam kerangka Technological Pedagogical Content Knowledge (TPACK) menjadi salah satu faktor utama yang menghambat pemanfaatan AI dalam pembelajaran. Untuk menjawab kebutuhan tersebut, program pelatihan ini dirancang guna memperkuat TPACK guru dalam menerapkan AI-integrated STEM-PBL, sehingga dapat meningkatkan kualitas pembelajaran sekaligus mendukung pencapaian SDG 4 (Kualitas Pendidikan). Kegiatan pelatihan dilaksanakan melalui workshop interaktif dan kegiatan praktik langsung (hands-on activities), dan pendampingan dengan melibatkan mahasiswa sebagai mitra kolaborasi antara perguruan tinggi dan sekolah. Hasil kuesioner menunjukkan seluruh peserta merasa pelatihan ini membantu mereka dalam memahami penerapan TPACK dan STEM-PBL, sementara 80% peserta menilai Abstract The rapid development of Artificial Intelligence (AI) has opened significant opportunities for innovation in STEM (Science, Technology, Engineering, and Mathematics) education through Problem-Based Learning (PBL). In general, teachers continue to face challenges in integrating this technology into classroom practice, particularly those working in regions located farther from urban centers, even though educational facilities have begun to improve. Limited understanding and skills within the Technological Pedagogical Content Knowledge (TPACK) framework remain key factors hindering the effective use of AI in teaching and learning. To address these needs, a training program was designed to strengthen teachers’ TPACK in implementing AI-integrated STEM-PBL, thereby enhancing teaching quality and supporting Sustainable Development Goal 4 (Quality Education). The program consisted of interactive workshops, hands-on activities, and mentoring, with the involvement of university students to foster collaboration between higher education institutions and schools. Questionnaire results indicated that all participants found the training useful in helping them to understand the application of TPACK and STEM-PBL, while 80% reported improvement in their TPACK skills and increased their confidence in using AI for their job as a teacher. These findings demonstrate the importance of systematic training in equipping teachers with AI-integrated STEM-PBL competencies and advancing technology-driven educational transformation in secondary schools. Keywords: Artificial Intelligence; STEM Education; TPACK; Teacher Training; Problem-Based Learning